Public policies in children’s mental health: Ways to promote health - Cruz, Elisian Macêdo Fechine da; Lima, Ana Flávia freire Tavares; Alves , Sabrina Alaide Amorim; Jastrow, Juliana Maria Bello; Elbani, Ana Carolina Lopes; Bezerra, Italla Maria Pinheiro (Seven Editora, 2023)
The study aimed to reflect on the evolutionary process of public policies on mental health for children. This is a theoretical essay with a reflective nature. The proposed reflections were based on relevant international and national literature. Anxiety Disorders become increasingly common in children, causing negative impacts on various cognitive and learning functions. It is concluded that it is necessary to develop and strengthen public policies in mental health, which are capable of reorienting care practices regarding the prevention of mental disorders in childhood. DOI:https://doi.org/10.56238/globalhealthprespesc-004